2021
DOI: 10.1016/j.toxrep.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Gastro protecting influence of Topiramate in ethanol produced gastric ulcers in rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(60 reference statements)
1
7
0
Order By: Relevance
“…In addition to the biochemical evaluations, in the present study, the macroscopic examinations indicated that pretreatment with topiramate reduced ulcer area and decreased the indomethacin-induced ulcer severity and these ameliorative effects were also observed in histopathologic examinations. These results are in line with the recent study of Kadasah et al 57 who reported a similar effect for topiramate in a rat model of experimentally ethanolinduced gastric mucosal damage. They reported that pretreatment with topiramate ameliorated ethanol-induced gastric damage in rats by inhibiting neutrophil infiltration, inflammation, and apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the biochemical evaluations, in the present study, the macroscopic examinations indicated that pretreatment with topiramate reduced ulcer area and decreased the indomethacin-induced ulcer severity and these ameliorative effects were also observed in histopathologic examinations. These results are in line with the recent study of Kadasah et al 57 who reported a similar effect for topiramate in a rat model of experimentally ethanolinduced gastric mucosal damage. They reported that pretreatment with topiramate ameliorated ethanol-induced gastric damage in rats by inhibiting neutrophil infiltration, inflammation, and apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, ethanol can impede the stomach's capacity to shield itself from injuries by minimizing the production of protective mucus and intensifying the permeability of its lining. These impacts are attributed to ethanol‐induced modifications in the levels of several substances, such as cytokines, prostaglandins, and ROS (Kadasah et al, 2021; Park et al, 2020).…”
Section: Effect Of Turmeric and Curcumin On Ethanol Toxicitymentioning
confidence: 99%
“…Reactive Oxygen Species (ROS) and other inflammatory mediators are overproduced at the site of stomach injury by white blood cells such as neutrophils, which also cause oxidative damage and cell damage 8,9 . Superoxide Dismutase (SOD) and Catalase (CAT), two antioxidant enzymes, as well as the non-enzymatic antioxidant Glutathione (GSH), are less active when Reactive Oxygen Species (ROS) are present 10 . These are some of the factors that contribute to the development of acute gastric ulcers brought on by ethanol and cause cell membrane damage.…”
Section: Introductionmentioning
confidence: 99%